2000
DOI: 10.1097/00005537-200010000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Schwannoma Growth: The Continuing Controversy

Abstract: Combined with other factors, the achieved results should be considered when timing of surgery is to be decided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…15,35 When it comes to volumetric versus diametric measurements of tumor, while some authors have stressed that volumetric determination is a reliable measure of tumor size and minimizes the risk of error due to partial volume effects, 19,35 other investigators have found no differences in growth results between measurements of tumor volume and tumor diameter. 11 Volumetric determination also requires expertise and an imaging technique that may not be available at all centers.…”
Section: Terminology Of Incomplete Resections and Algorithmmentioning
confidence: 99%
“…15,35 When it comes to volumetric versus diametric measurements of tumor, while some authors have stressed that volumetric determination is a reliable measure of tumor size and minimizes the risk of error due to partial volume effects, 19,35 other investigators have found no differences in growth results between measurements of tumor volume and tumor diameter. 11 Volumetric determination also requires expertise and an imaging technique that may not be available at all centers.…”
Section: Terminology Of Incomplete Resections and Algorithmmentioning
confidence: 99%
“…They commonly occur on the vestibular branch of the eighth cranial nerve but can arise anywhere in the periphery. Vestibular schwannomas (VS) account for up to 8% of all intracranial tumors [1] . About 95% of VS occur sporadically and unilaterally, while about 5% occur as part of the inherited disorder neurofibromatosis type 2 (NF2), an autosomal-dominant disorder with an incidence of approximately 1 in 33,000-40,000 individuals [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In case of a solid VS a wait-and-scan-policy is often appropriate because these tumors in general show no growth or have a slow growth pattern, varying between 0.9 and 1.9 mm in maximal diameter per year [1][2][3][4]. Moreover, several studies on the growth rate of VSs, have shown besides stability even regression during conservative management [1,[5][6][7][8][9][10]. In contrast, part of the solid VSs is able to present with relatively rapid growth, which eventually might result in serious morbidity and even mortality if left untreated.…”
Section: Introductionmentioning
confidence: 99%